The effect of self-image, peer Influence and man-nature orientation toward sustainable shopping behaviour among undergraduate students in Klang Valley - Adna, Nor Rasyidah; Leby Lau, Jasmine (Human Resource Management Academic Research Society, 2023)
The negative effects of linear economics are manifesting themselves in the form of deteriorating environmental quality. Following this, more consumers are beginning to shift to sustainable way of shopping. The objectives of this research were to investigate the relationship between each of self-image, peer influence, and man-nature orientation toward consumer’s sustainable shopping behaviour and to determine the factor(s) that significantly predict the shopping behaviour. Data were collected from 210 undergraduate students from Universiti Putra Malaysia (UPM) and Universiti Teknologi MARA (UiTM) campuses located within Klang Valley. Correlation analyses shown that all three determinant factors were positively correlated with sustainable shopping behaviour. Multiple regression results revealed that peer influence has the most effect on sustainable shopping behaviour, followed by man-nature orientation and self-image. It is suggested that companies should focus on developing and positioning products that provide positive experience so that these young consumers could recommend it to peers through word of mouth. In addition, businesses also need to focus on eco-packaging and green attributes of the product that enhance self-image and sustainability orientation within the young consumers.